The scalings of the thermal energy confinement time in EAST H-mode plasmas. (1st March 2023) - Jia, T.Q.; Qian, J.P.; Chen, D.L.; Moreau, D.; Shen, B.; Zhang, B.; Gong, X.Z.; Huang, J.; Zhang, J.Y.; Yang, X.D.; Liang, R.R.; Hu, Y.C.; et al.
Abstract: This paper describes scalings of the H-mode confinement database of neutral beam injection (NBI)-lower hybrid wave (LHW) and electron cyclotron resonant heating-LHW plasmas in the EAST tokamak. Fundamental information of the EAST H-mode database and the details of calculation of the thermal energy confinement time in EAST are presented. The result of the scaling model τ E, EASTS, H, NBI - LHW of the thermal energy confinement time in NBI-LHW plasmas with root-mean-square-error RMSE = 5.5 %, compared with the multi-machine scaling model τ th, 98 y 2 derived from the multi-machine database (mainly NBI heating) with RMSE = 12.9 %, is obtained. The scaling τ E, EAST, H, NBI - LHW presents a similar dependency on plasma current and power loss and a lower dependency on plasma density and elongation, but stronger dependency on toroidal field than in τ th, 98 y 2 . The scaling τ E, EAST, H, ECRH - LHW demonstrates a similar dependency on plasma current and power loss and lower dependency on plasma density, but a negative dependency with large error bars on elongation compared with τ E, EAST, H, NBI - LHW in NBI-LHW plasmas. The comparison of EAST models with the more recent multi-tokamak scaling ITPA20-IL shows a similar engineering dependency on plasma current, power loss and plasma density, but opposite dependency on toroidal field.